PERANAN IMAM SYAFIâ€™I DALAM PENGEMBANGAN HADIS - Muttaqin, Zainal (SAMAWAT: Journal Of Hadith and Qur’anic Studies, 2019)
The efforts made by Hadith Experts from time to time are quite diverse and different in terms of the demands of the conditions and circumstances of the time. The birth of Imam Shafi'i (150-204 H) in this century contributed so much to the intellectual treasures of Islam, especially in the field of hadith. This figure who is known to be moderate and accommodative in addition to having capabilities in the science of ushul-al-fiqh he also has capabilities in hadith, in fact he is the founder of the foundations of these two branches. His fame can be seen from several works that he scratched, including al-Umm, al-Risalah, Ikhtilaf al-Hadith. Imam Shafi'i at the time was known as Nashir al-Sunnah/ assistant of the Sunnah of the Prophet. The honorary titles bestowed on scholars from the cities of Baghdad and Makkah show his great contribution to the Sunnah. Apart from maintaining the authenticity of the hadith, its contribution is very big in maintaining the Sunnah from the hands of Munkir al-Sunnah who rejects the hadith as a religious argument. According to Muhammad Syakir, al-Syafi'i is the founder of the epistemological foundations of Hadith